Scalable, safe, high-rate supercapacitor separators based on the Al2O3 nanowire Polyvinyl butyral nonwoven membranes. (May 2020) - Liu, Mengting; Turcheniuk, Kostiantyn; Fu, Wenbin; Yang, Yang; Liu, Michael; Yushin, Gleb
Abstract: High-performance supercapacitor nonwoven separators based on polyvinyl butyral (PVB) with uniformly distributed Al2 O3 nanowires (NW) fillers (up to 40 wt %) have been developed using a low-cost casting (stir-pour-dry) technique utilized under ambient conditions for the first time. These novel nonwoven separators with highly porous network demonstrated tensile strength of >30 MPa, extremely high electrolyte absorption (>200 wt. %), low-to-no swelling behavior and stable electrochemical performance, substantially exceeding that of analogous cells with commercial separators. Thermal properties of the produced separators were also exceptional with >15 MPa of ultimate strength, high flexibility and minimal thermal shrinkage maintained at temperatures as high as 200 °C. The one-dimensional (1D) ceramic nanofillers improved PVB's mechanical and thermal properties and enabled formation of highly porous membranes with self-organized nanopores and high ionic conductivity of up to 13.5 mS/cm in 1 M Na2 SO4 aqueous electrolyte. This simple and innovative method and separator design is attractive for manufacturing of high-strength, low-cost and flexible separators and suitable for various polymers-ceramic nonwoven compositions for fast charging, high-power and safe electrochemical capacitors, hybrid devices and batteries. Graphical abstract: Image 1 Highlights: Composite Al2 O3 NW-PVB membrane was successfully prepared by a very simple, highly scalable and ultralow-cost technique. The membraneswith highly porous structure demonstrated enhanced mechanical strength, wetting and electrochemical performance. High ionic conductivity of up to 13.5 mS/cm in aqueous electrolyte was demonstrated. Stable performance was obtained due to its high porosity, excellent electrolyte wetting and fast ion transport. This reported innovation paves ways for designing next generation separators for faster charging, higher power and safer devices.